Epidural analgesia for percutaneous kyphoplasty in a patient with multiple medical comorbidities - Waseem S Alfahel (Thieme Medical and Scientific Publishers Pvt. Ltd., 2019)
Kyphoplasty is a minimally invasive procedure intended to stabilize the fractured bone and restore bone height. It involves percutaneous introduction of an inflatable bone tamp into a fractured vertebral body, followed by injection of bone cement into the ballooned pocket. Anesthetic options typically considered for this procedure include intravenous sedation or general anesthesia. These patients are often elderly, frail, in significant pain, and may poorly tolerate sedation or general anesthesia in the prone position. Spinal anesthesia has been suggested as an alternative method. However, it has major limitations. We would like to report a case of a 79-year-old patient with multiple comorbidities, who presented for kyphoplasty, where epidural anesthesia was conducted and successfully provided adequate analgesia as well as optimal surgical conditions. Key messages: Epidural anesthesia can provide successful operating conditions for kyphoplasty. General anesthesia need not be a default technique in medically complex patients. There may be many other procedures where regional techniques may provide surgical anesthesia.